2006
DOI: 10.1039/b604140j
|View full text |Cite
|
Sign up to set email alerts
|

Reactions of alkyl-radicals with gold and silver nanoparticles in aqueous solutions

Abstract: Silver and gold nanoparticles are very efficient catalysts for the dimerization of methyl-radicals in aqueous solutions. The rate constants for the reaction of methyl-radicals with the gold and silver nanoparticles were measured and found to be 3.7 x 10(8) M(-1) s(-1) and 1.4 x 10(9) M(-1) s(-1), respectively. The results thus suggest that alkyl-radicals, also not reducing ones, are scavenged by these nanoparticles. This might explain the role, if such a role exists, of these nanoparticles in medical applicati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
75
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 47 publications
(80 citation statements)
references
References 13 publications
4
75
0
Order By: Relevance
“…In the present study, we also used electron microscopy of the pancreas and investigated the effects of AuNP treatment on diabetic rats with autism. It has been suggested that islet cells may arise from exocrine cells [46][63]. Our observations of granules in the Golgi zone of beta cells of diabetic rats suggest that the synthesis of some secretory material continues to take place in the beta cell.…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…In the present study, we also used electron microscopy of the pancreas and investigated the effects of AuNP treatment on diabetic rats with autism. It has been suggested that islet cells may arise from exocrine cells [46][63]. Our observations of granules in the Golgi zone of beta cells of diabetic rats suggest that the synthesis of some secretory material continues to take place in the beta cell.…”
Section: Discussionsupporting
confidence: 50%
“…However, the chemical reactivity of gold particles at diameters of less than 3 nm is most likely different than it is for larger gold nanoparticles [45]. Zidki et al [46] reported a potential radical scavenging property of gold nanoparticles against alkyl radicals. Zhang et al [47] also observed a reduction in the EPR signal (indication of radical scavenging) following the interaction of free radicals with 15 nm gold nanoparticles.…”
Section: Discussionmentioning
confidence: 99%
“…After the irradiation, the gas phase was analysed by gas chromatography as described elsewhere. [19] The error limits on the yields of the final products thus determined were AE 15 %. Yields were calculated by assuming that all the methyl radicals are formed in the aqueous phase, that is, that the energy absorbed by the titania is not transferred to the solution and does not contribute to radical formation.…”
Section: Introductionmentioning
confidence: 98%
“…Recent results indicate that alkyl, [18,19] substituted alkyl [20] and alkylperoxyl [21] radicals react very quickly with metal NPs [19,21] and powders [18,20] in aqueous solutions to form transients in which the radicals are bound to the NPs through s bonds. The mechanism for the decomposition of these transients to yield the final products depends on the nature (and the particle size) of the metal, the substituents on the radical and the composition of the solution.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation